Scaffold-mediated delivery for non-viral mRNA vaccines. Issue 8 (December 2018) - Chen, Ruying; Zhang, Hong; Yan, Jingxuan; Bryers, James
Abstract mRNA is increasingly being recognized as a promising alternative to pDNA in gene vaccinations. Only recently, owing to the needs of cancer immunotherapies, has the biomaterials/gene delivery community begun to develop new biomaterial strategies for immunomodulation. Here, we report a novel way to use implantable porous scaffolds as a local gene delivery depot to enhance mRNA vaccine immunization in vitro, and in vivo when compared with conventional bolus injections. We first evaluated transfection efficiencies of single-stranded mRNA condensed and charge neutralized with two lipids (Lipofectamine Messenger MAXTM LM-MM and StemfectTM SF) and two cationic polymers (in vivo-jetPEI™, Poly (β-amino ester)) as gene carriers. As SF demonstrated highest in vitro transfection and cell viability, it was selected for subsequent porous polymer scaffold-loading trials. Enhanced in vitro transfection of SF:mRNA nanoparticle-loaded poly (2-hydroxyethyl methacrylate) (pHEMA) scaffolds was also observed with a DC2.4 cell line. Improved sustained local release and local transgene expression were also demonstrated with SF:mRNA nanoparticle-loaded pHEMA scaffolds in vivo compared with bolus injections. Our results suggest that mRNA polyplex-loaded scaffolds may be a superior alternative to either repeated bolus immunizations or ex vivo transfection cell immunotherapies.